The Conflict Between the Sebambangan Marriage Tradition of the Indigenous Lampung Community and the Implementation of Premarital Course Regulations - Nabil Nizam; Fitri Maulina Alviani; Sadida Nizam (Universitas Muhammadiyah Bandung, 2025)
The premarital course is a government-initiated program aimed at preparing prospective couples to establish harmonious, loving, and compassionate families (sakinah, mawaddah, warahmah), and to reduce divorce rates in Indonesia. Regulated by the Decree of the Director General of Islamic Community Guidance No. DJ.II/542 of 2013, the Office of Religious Affairs (KUA) is mandated to provide a 16-hour premarital course before the marriage contract. However, implementation in areas with strong local traditions presents specific challenges. This study investigates the implementation of the premarital course within the indigenous Lampung community in Marga Tiga District, where the traditional practice of sebambangan a secretive elopement of the bride to the groom's house still occurs. This tradition prohibits the bride from leaving her home before the wedding, hindering in-person participation in the course. Employing an empirical normative legal research method with a qualitative approach, data were gathered through field observations and interviews with KUA officials, traditional leaders, and prospective couples. The findings reveal that the implementation of the premarital course remains suboptimal due to cultural constraints, limited access, and a lack of alternative dissemination methods tailored to local conditions. The study suggests the need for innovative solutions, such as online platforms or home-accessible media, to enhance the accessibility and effectiveness of premarital education among indigenous communities.